Aplicação materna de glicocorticoide nos parâmetros vitais de cordeiros nascidos a termo e prematuros - Bovino, Fernanda [UNESP]; Avila, Larissa Gabriela [UNESP]; Deschk, Maurício [UNESP]; Mendes, Luiz Cláudio Nogueira [UNESP]; Santos, Guilherme Gonçalves Fabretti [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP]; Camargo, Diogo Gaubeur de [UNESP]; Souza, Natalia Cristina de [UNESP] (Univ Federal Santa Maria, 2014)
The aim of the study was to evaluate the influence of glucocorticoids on vital parameters of full-term and preterm lambs from birth to 48 hours of life. Four experimental groups were formed: NDG (normal delivery group - lambs vaginally delivered, n=15, average of 146-day gestation); NDEXG (normal delivery with dexamethasone group - lambs vaginally delivered whose mothers received 16mg of dexamethasone at 141 days of gestation, n=8, average of 143-day gestation); PRE (premature lambs born by cesarean section at 138 days of gestation, n=10) and PREDEX (premature lambs born by cesarean section at 138 days gestation, whose mothers received 16mg of dexamethasone two days before, n=9). Heart and respiratory rates had variations during the observation period, with the highest mean values in the groups of normal deliveries (NDG and NDEXG). Rectal temperature decreased in all groups in the first 60 minutes of life, with the lowest mean values in premature lambs (PRE and PREDEX) and the Apgar score was higher in animals delivered at normal gestational time. Preterm lambs had lower vitality and chance of survival, however, lower mortality rate was observed in offspring of ewes that received dexamethasone two days before surgery.

O objetivo deste trabalho foi avaliar a influência do glicocorticoide sobre parâmetros vitais de cordeiros nascidos a termo e prematuros, do nascimento às 48 horas de vida. Foram constituídos quatros grupos: PN (cordeiros nascidos de parto normal, n=15, média de 146 dias); PNDEX (cordeiros nascidos de parto normal, cujas mães receberam 16mg de dexametasona aos 141 dias de gestação, n=8, média de 143 dias); PRE (cordeiros prematuros nascidos de cesarianas aos 138 dias de gestação, n=10); e PREDEX (cordeiros prematuros nascidos de cesarianas aos 138 dias de gestação, cujas mães receberam 16mg de dexametasona dois dias antes, n=9). As frequências cardíaca e respiratória variaram ao longo do período, com os maiores valores nos grupos de partos normais. A temperatura retal diminuiu em todos os grupos nos primeiros 60 minutos de vida, sendo os menores valores observados nos cordeiros prematuros, e o escore Apgar foi mais alto nos animais nascidos em tempo gestacional normal. Os cordeiros prematuros apresentaram menor vitalidade e menor taxa de sobrevivência, entretanto, menor taxa de mortalidade foi observada nos prematuros sob influência da dexametasona.
Maternal glucocorticoid in vital parameters of full-term and preterm lambs
Keywords: Apgar; Dexamethasone; Lambs; Premature; Vitality